Values and Attitudes Toward Social and Environmental Accountability: a Study of MBA Students - Fukukawa, Kyoko (Journal of business ethics, 2007)
Efforts to promote corporate social and environmental accountability (SEA) should be informed by an understanding of stakeholders’ attitudes toward enhanced accountability standards. However, little is known about current attitudes on this subject, or the determinants of these attitudes. To address this issue, this study examines the relationship between personal values and support for social and environmental accountability for a sample of experienced MBA students. Exploratory factor analysis of the items comprising our measure of support for SEA revealed two distinct factors: (1) endorsement of the general proposition that corporations and executives should be held accountable for the social and environmental impacts of their actions; and (2) agreement that the government should adopt and enforce formal SEA standards. Our findings indicate that the universalism value type is positively associated with general support for SEA, but not with support for government enforcement of accountability standards. In addition, we found that gender has a significant impact on support for government enforcement of SEA standards.